Food ingredients from the marine environment. Marine biotechnology meets food science and technology - Boziaris, Ioannis S. (Frontiers in Marine Science, 2014)
Marine environment disposes a plethora of bioactive compounds with unique properties and remarkable potential for biotechnological applications. A lot of those compounds can be used by the food industry as natural preservatives, pigments, stabilizers, gelling agents, etc., while others exhibits beneficial effects and can be used as functional food ingredients, nutraceuticals, dietary supplements and prebiotics. Interdisciplinary approach is required to increase our knowledge, explore the potential of marine environment and produce value-added food for all.